Primary versus staged reconstruction and risk of surgical failure in patients with ulcerative colitis:a nation-wide co hort study - Fu Zhaoyuan (结直肠肛门外科, 2022)
[Background] Restorative surgery after colectomy due to ulcerative colitis (UC) may be performed simultaneously with colectomy (primary) or as a staged procedure. Risk factors for failure after restorative surgery are not fully explored. This study aimed to compare the risk of failure after primary and staged reconstruction. [Methods] This is a national register-based cohort study of all patients 15 to 69 years old in Sweden treated with colectomy due to UC and who received an ileorectal anastomosis (IRA) or ileal pouch-anal anastomosis (IPAA) between 1997 and 2017. Failure was defined as a reoperation with new ileostomy after restorative surgery or a remaining defunctioning ileostomy after 2 years. Risk of failure was calculated using the Kaplan-Meier method and Cox regression adjusted for sex, age, calendar period, primary sclerosing cholangitis, and duration of UC. [Results] Of 2172 included patients, 843 (38.8%) underwent primary reconstruction, and 1329 (61.2%) staged reconstruction. Staged reconstruction was associated with a decreased risk of failure compared with primary reconstruction (hazard ratio, 0.73; 95% CI, 0.58-0.91). The 10-year cumulative risk of failure was 15% vs 20% after staged and primary reconstruction, respectively. In all, 1141 patients (52.5%) received an IPAA and 1031 (47.5%) an IRA. In stratified multivariable models, staged reconstruction was more successful than primary reconstruction in both IRA (hazard ratio, 0.75; 95% CI, 0.54-1.04) and IPAA (hazard ratio, 0.73; 95% CI, 0.52-1.01), although risk estimates failed to attain statistical significance. [Conclusions] In UC patients undergoing colectomy, postponing restorative surgery may decrease the risk of failure.